Where Do All the Attacks Go? - Florencio, Dinei; Herley, Cormac (2011)
The fact that a majority of Internet users appear unharmed each year is difficult to reconcile with a weakest-link analysis. We seek to explain this enormous gap between potential and actual harm. The answer, we find, lies in the fact that an Internet attacker, who attacks en masse, faces a sum-of-effort rather than a weakest-link defense. Large-scale attacks must be profitable in expectation, not merely in particular scenarios. For example, knowing the dog's name may open an occasional bank account, but the cost of determining one million users' dogs' names is far greater than that information is worth. The strategy that appears simple in isolation leads to bankruptcy in expectation. Many attacks cannot be made profitable, even when many profitable targets exist. We give several examples of insecure practices which should be exploited by a weakest-link attacker but are extremely difficult to turn into profitable attacks.